URGENSI PEMBENTUKAN PENGADILAN KHUSUS EKONOMI SYARIAH DALAM LINGKUNGAN PERADILAN AGAMA - Saut Maruli Tua Manik (JOURNAL EQUITABLE, 2021)
The importance of a special sharia economic court in the Religious Courts is reviewed philosophically, sociologically, juridically. Philosophically it is based on Pancasila as the state philosophy. The sociological basis of the sharia economics special court answers problems and fulfills the needs of Islamic religious law in the field of sharia economics on the basis of empirical facts of sharia economic dispute resolution, juridically based on Article 3A of Law Number 3 of 2006, and Article 3A paragraphs (1), (3) and 13B paragraph (1) of Law Number 50 of 2009 concerning the Second Amendment to Law Number 7 of 1989 concerning the Religious Courts. Problem: What are the efforts and obstacles that the Supreme Court does to improve the quality of sharia economic dispute resolution in the Indonesian Religious courts. Normative methodology with a normative juridical approach. Data sources are primary data and supported secondary data